An advanced cathode material for high-power Li-ion storage full cells with a long lifespan. Issue 39 (24th September 2019) - Huang, Haijian; Pan, Long; Chen, Xi; Tervoort, Elena; Sologubenko, Alla; Niederberger, Markus
Abstract : Combination of materials with fast Li-ion storage in both positive and negative electrodes results in a high-rate lithium ion battery full cell with a long life-span. Abstract : Compared to the progress made in high-rate anodes, the exploration of cathode materials with comparable performance remains a challenge in the fabrication of high power Li-ion storage devices. Here a cathode material with fast Li-ion storage is reported, which is composed of Ni0.25 V2 O5 · n H2 O nanobelts with a layered structure and reduced graphene oxide. Operando X-ray diffraction and ex situ X-ray photoelectron spectroscopy results reveal an electrochemical process with high structural reversibility during charging/discharging. Kinetics analysis based on cyclic voltammetry measurements demonstrates fast Li-ion storage in the cathode material. These positive properties lead to high rate capability and cycling stability of the composite. Even at a high mass loading of 11.3 mg cm −2, the material still offers high-performance Li-ion storage, indicating its great promise for practical applications. Furthermore, we report for the first time the combination of such a high-rate cathode with a surface redox pseudocapacitive anode made of N-doped reduced graphene oxide foam for a fast-charging Li-ion storage full-cell device with a long lifespan. The high performance of the full cell suggests that the concept of using materials with fast Li-ion storage in both the positive and negative electrodes represents a promising strategy to develop high-power and high-energy Li-ion storage devices.